AVALIAÇÃO DA ESTABILIDADE DE COR DE LAMINADOS CERÂMICOS APÓS CIMENTAÇÃO ADESIVA - Sakamoto Junior, Antonio Setsuo (2015)
Thin ceramic laminates have been widely requested by patients because it’s a reliable conservative aesthetic procedure, stable and presents adequate longevity. It is known that the color change of the cement below these thin restorations may result inappropriate final color. Thus, the purpose of this in vitro study was to evaluate the color agreement between pressable lithium disilicate ceramics with tryin pastes and corresponding resin cements, determination of the degree of conversion of resin cements using FT-Raman spectroscopic and color stability after artificial accelerated aging (AAA) for 300 hours. Eighty-four ceramic discs (0.3 mm, 0.5 mm, 1.0 mm thick) were prepared (IPS e.maxPress HT A2 – Ivoclar Vivadent) to simulate veneers. Evaluation the baseline color was done in the CIE-L*a*b* color space with reflectance spectrophotometer (control group). The try-in pastes were applied into the interlayer of the ceramic (simulation of selection color procedure) above silicon transparent matrix (0.1 mm thick) and the color complex were measured using a spectrophotometer (n=7), with no substrate. The same ceramic discs were used for cementation procedure with Variolink II (only base),after storage in distilled water, protected from light, at 37ºC for 24 hours, the specimens were mensured the color and submitted to FT-Raman spectroscopy to determinate the degree of conversion (DC). After that, the specimens were AAA for 300 hours and measured by spectrophotometer to calculate ΔE. Two-way ANOVA was used to analyze the data. Tukey’s post hoc for multiple comparisons and Spearman correlation test were performed (α = 0.05). There was no agreement between the try-in with resin cements, L* and b* values increased, increasing the value/opacity,yellowish of the complex. All groups exhibited values of ΔE>3.3, except resin color A3 group (1.0 mm ceramic thickness). Ceramic thicknesses (0.3 mm and 0.5 mm) did not affect the DC compared to the control (p> 0.05). Thus, DC was influenced by the color of cement, where the over saturated color showed higher conversion rate, DC decreased when ceramic disc thickness increased. No correlation between DC and ΔE was observed.